Structural investigation of α-l-fucosidase from the pancreas of Patiria pectinifera, based on molecular cloning. (1st March 2019) - Ono, Akiko; Suzuki, Tomohiro; Gotoh, Saki; Kono, Haruka; Matsui, Megumi; Aoki, Daichi; Matsuda, Masaru; Kawagishi, Hirokazu; Ogata, Makoto
Abstract: An α-l -fucosidase (Pap-Alf) was purified from the pancreas of a starfish Patiria pectinifera by ammonium sulfate precipitation followed by several column chromatographies. The molecular mass of the purified enzyme was estimated to be 52.6 kDa by SDS-PAGE, although gel filtration analysis of the native enzyme suggests it exists as a homodimer in solution. The purified enzyme showed maximal activity at pH 5.0 and 70 °C. The enzyme was highly specific toward a fucosyl-monosaccharide (Fuc-α- p NP), but it also showed activity toward 2-sulfo-Fuc-α- p NP and fucosyl-α-lactosides (Fuc-α-Galβ1→4Glc-β- p NP). We determined the primary structure of the α-l -fucosidase and validated its expression level in starfish tissue. Whole genome sequence analysis of P. pectinifera was also performed in the present study. Detailed primary structural analysis using bioinformatics tools revealed Pap-Alf lacks the C-terminal region that is otherwise conserved in all previously described α-l -fucosidases. Quantitative gene expression analysis of Pap-Alf in each tissue indicated that the expression of Pap-Alf gene in pancreas was 5-fold higher than in ovary. Graphical abstract: Image 1 Highlights: We succeeded in the purification of the novel α-l -fucosidase (named Pap-Alf) from the pancreas of Patiria pectinifera. The primary structure of Pap-Alf was identified by LC-MS/MS based on genomic information of starfish obtained. Pap-Alf possessed unique structural features, which lacks the C-terminal region conserved.